Revision of Dimelaena Norman (Caliciaceae, Ascomycota) species containing usnic acid reveals a new species and a new combination from China - Ai, Min; Zhong, Qiuyi; Scheidegger, Christoph; Wang, Lisong; Wang, Xinyu (Phytotaxa, 2022)
Dimelaena tibetica is described as a species new to science, characterized by a grayish yellow surface, usually with a covering of white pruina, a crustose thallus, areolate at center, radiate-plicate at margin, adnate apothecia and lacking gyrophoric acid. It differs from other usnic acid-containing Dimelaena species by its plane marginal lobes and adnate apothecia. Based on the study of fresh specimens from the environment of the type locality, Dimelaena altissima is proposed as a new combination. A fresh specimen of Dimelaena oreina (type species of the genus Dimelaena) was collected in the Swiss Alps, in the vicinity of the area where the type material of the species presumably was collected, and a sequence was generated to confirm the phylogenetic position of this genus. All three species share common characters: usnic acid content and a yellowish green upper surface. Descriptions of these species were based on a combination of morphological and phylogenetic analyses. A key and phylogram are provided for these three Dimelaena species which produce usnic acid.